Supply Chain Management in Competitive Structure of Sochi Health Resort and Spa Industry: Strategic Groups Analysis - Nelli A. Saveleva; Tatyana A. Yudina; Olga G. Kovalenkova; Urii I. Verbin; Violetta V. Rokotyanskaya (International Journal of Supply Chain Management, 2020)
Abstract- In the health industry, distribution model, customers, and product catalog pose a unique set of problems for your supply chain. The article discusses the identification of strategic groups within health and resort services market based on the suuply chain strategiers. Segmentation of competitors included the following steps: establishing mobility barriers; classification of sanatoriums and health resorts taking into account the mobility barriers; identification of strategic groups; description of strategic groups existing in the market of health-resort and spa services. Five strategic groups were identified. Recommendations on the selection of competitive strategies were made for each group. The results of strategic grouping can be used in forming competitive advantages allowing to successfully compete with rival firms in spa market. The article presents the results of the research supported by grant ? 19-410-230059r_a from the Russian Foundation for Basic Research.